2006
DOI: 10.1002/ijc.21340
|View full text |Cite
|
Sign up to set email alerts
|

ZD6474 inhibits tumor growth and intraperitoneal dissemination in a highly metastatic orthotopic gastric cancer model

Abstract: Angiogenesis inhibitors have been used to treat some cancers, but the therapeutic potential of these agents for gastric cancer has remained unclear. To investigate their therapeutic potential, we examined the effect of ZD6474, an agent that selectively targets vascular endothelial growth factor receptor-2 (VEGFR-2; KDR) tyrosine kinase and epidermal growth factor receptor (EGFR) tyrosine kinase, in a highly metastatic orthotopic model using an undifferentiated gastric cancer cell line, 58As1. ZD6474 (100 mg/ k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…* Genes that have no designated gene symbol. endothelial growth factor receptor inhibition which resulted in decreased vascularity and increased hypoxia (27). However, a study by Ito and colleagues showed that a mouse that overexpressed ANGPTL4 showed inhibition of colorectal xenograft tumor growth and decreased vascularity within the tumors (26).…”
Section: Discussionmentioning
confidence: 99%
“…* Genes that have no designated gene symbol. endothelial growth factor receptor inhibition which resulted in decreased vascularity and increased hypoxia (27). However, a study by Ito and colleagues showed that a mouse that overexpressed ANGPTL4 showed inhibition of colorectal xenograft tumor growth and decreased vascularity within the tumors (26).…”
Section: Discussionmentioning
confidence: 99%
“…Oligonucleotide microarray study and microarray analysis A microarray procedure was performed as described previously (Arao et al, 2006). In brief, total RNA extracts were collected from A549 cells transfected with ATF4 siRNA (50 or 0.3 nM) or control siRNA (50 or 0.3 nM) in duplicate.…”
Section: Knockdown Analysis Using Sirnasmentioning
confidence: 99%
“…In this study, we used mouse models with orthotopically transplanted human scirrhous gastric cancer cells showing spontaneously progressing peritoneal dissemination, which we reported previously (18,19,21). These models can imitate more realistically the progressing mode of human peritoneal dissemination of gastric cancer than conventional experimental models directly transplanted with cancer cells i.p.…”
Section: Discussionmentioning
confidence: 99%
“…44As3 and 58As1m were previously reported as human signet-ring cell gastric cancer cell lines that spontaneously metastasize to the peritoneal cavity and produce large volumes of bloody ascites after orthotopic implantion in the gastric wall (18)(19)(20)(21). Here, 44As3 and 58As1m cells were transfected with a complex of 4 Ag of pEGF-PLuc plasmid DNA (Clontech) and 24 AL of GeneJammer reagent (Stratagene; Cloning Systems) in accordance with the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation